Expression of a Lipid Transfer Protein in Escherichia coli and Its Phosphorylation by a Membrane-Bound Calcium-Dependent Protein Kinase - Martin, Mariana Laura (2007)
Ha-AP10 is a basic antifungal peptide from sunflower seeds (Helianthus annuus antifungal peptide of 10 kDa) belonging to the family of plant lipid transfer proteins. We report here its expression in E. coli [Glutathione S-transferase (GST) system] and its phosphorylation by endogenous membrane-bound calcium-dependent protein kinases.